Study of Oligohydramnios and its perinatal outcome - Patil, Sudha V.; Shaikmohammed, Fatima Zahra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Importance of amniotic fluid volume as an indicator of fetal status is being appreciated relatively recently. Around 3% to 8% of pregnant women are presenting with low amniotic fluid at any point of pregnancy. The present study was undertaken to study the outcome of pregnancies with Oligohydramnios [(amniotic fluid index) AFI≤5cm] at or beyond 34 weeks. Methods: This study consists of 50 cases of antenatal patients with oligohydramnios (AFI≤5) at or beyond 34 weeks of gestation compared with age and gestation matched 50 normal liquor (AFI≥5 and ≤25). The outcome measures recorded were labor, gestational age at delivery, amniotic fluid index (AFI), mode of delivery, indication for cesarean section or instrumental delivery, APGAR score and birth weight. Results: In the present study, AFI was significantly decreased in cases (3.74±1.2) compared (12.54±2.5) with controls. Variable deceleration was noted in 14 (28%) and late deceleration in 5 (10%) cases. In control group, 2 (4%) had late deceleration. In cases induced labor is in 14 (28%), spontaneous labor 36 (72%). In cases, term normal vaginal delivery was in 15 (30%), PVD in 6 (12%), LSCS in 28 (56%) and instrumental vaginal delivery in 1 (2%). In controls, full term normal vaginal delivery was in 41 (82%), PVD in 5 (10%), LSCS in 4 (8%). APGAR score <7 at 1 minute was in 19 (38%) and at 5 minutes was in 5 (10%) in cases. Birth weight is reduced in cases. IUGR was reported in 9 (18%) in cases. Conclusions: Pregnancies with Oligohydramnios (AFI≤5) is associated with increased rate of non-reactive NST. Routine induction of labor for Oligohydramnios is not recommended. It is preferable to allow patients to go into spontaneous labor with continuous FHR monitoring. Antepartum diagnosis of Oligohydramnios warrants close fetal surveillance.